VASN knockout induces myocardial fibrosis in mice by downregulating non-collagen fibers and promoting inflammation - Junming Sun; Siwei Yin; Qiurui Li; Jun Zhang; Xiaoping Guo; Na Yu; Bing Hu; Yiqiang Ouyang; Qiaojuan Huang; Min He; Min He; Min He (Frontiers in Pharmacology)
Myocardial fibrosis (MF) is an important cause of heart failure and cardiac arrest. Vasorin knockout (VASN−/−) leads to pathological cardiac hypertrophy (PCH); however, it is not yet clear whether this PCH transitions to MF in mice. VASN-knockout mice showed typical pathological, imaging, and molecular features of MF upon hematoxylin and eosin staining, Masson staining, Sirius red staining, quantitative polymerase chain reaction (qPCR), immunohistochemistry-paraffin (IHC-P), and immunofluorescence analyses. RNA was extracted from mouse heart tissue, identified, and sequenced in vitro. Differential analysis of the genes showed that the extracellular matrix (ECM) genes (COL6A1, COL9A1, and FRAS1) had strong correlations while their expression levels were significantly reduced by qPCR, IHC-P, and Western blotting. The expression levels of the ECM genes were significantly reduced but those of the inflammatory factors (IL1β and IL6) were significantly upregulated in the heart tissues of VASN-knockout mice. These preliminary results reveal that VASN knockout induces MF by regulating the non-collagen fibers and inflammation.